Efforts To Improve The School Library And Literacy Of Students/Students Of Sd Negeri 5 Rambang Village Sugih Waras Barat - Sahfitri, Meilia (UIN Raden Intan Lampung, 2024)
Research and community service programs in the form of education in collaboration with real work students from Raden Fatah State Islamic University, Palembang and Sugih Waras Barat Village, Rambang District, Muara Enim Regency. South Sumatra Province to provide teaching related to efforts to improve school libraries and student literacy at SD Negeri 5 Rambang, West Sugih Waras Village, Muara Enim Regency. The method used was subjective enlightenment methodology, the population in this study were children of SD Negeri 5 Rambang, West Sugih Waras Village with a total of 340 students. This method aims to improve the school library and student literacy at SD Negeri 5 Rambang, West Sugih Waras Village, increase interest in reading, writing and speaking so that students can develop their own potential. Data was collected directly at the location of SD Negeri 5 Rambang in Sugih Waras Barat Village. Re-improving the existing school library and improving literacy among students at SD Negeri 5 Rambang, Sugih Waras Barat Village, Muara Enim Regency